2015
DOI: 10.1007/s11249-015-0496-3
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a Tribo-Modified Surface Layer on SBR Elastomers: Balance Between Formation and Wear of the Modified Layer

Abstract: In most of the tribological contacts, the composition and tribological properties of the original interface will change during use. The tribo-films, with modified properties compared to the bulk, are dynamic structures that play a significant role in friction. The existence of a tribo-modified surface layer and its importance on the overall friction of elastomers has been shown both theoretically and experimentally before. The characteristics of the modified surface layer deserve specific attention since the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The existence of a modified surface layer is controlled by a competition between the formation rate of the surface layer and the wear rate [23]. Figure 8b shows the image of the wear process and formation process on the wear surface of the elastomer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a modified surface layer is controlled by a competition between the formation rate of the surface layer and the wear rate [23]. Figure 8b shows the image of the wear process and formation process on the wear surface of the elastomer.…”
Section: Resultsmentioning
confidence: 99%
“…This modification alters the interfacial shear stress during sliding contact and therefore influences the friction [ 16 ]. Recently, Mokhtari [ 23 ] suggested that the development of a modified surface layer of elastomers depends on the competition between the formation and removal of a surface layer during sliding contact.…”
Section: Introductionmentioning
confidence: 99%
“…The real area of contact can also play a significant role in determining the overall friction [32]. The real area of contact decreases with an increase in the sliding velocity, therefore the ratio between the real area of contact to the apparent contact area is shown for a sliding velocity of 5 mm/s to study the effect of transversely isotropy.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Frictional heating at high sliding velocities can result in softening of the rubber or even the formation of a thermochemical degraded layer on the rubber surface which can affect both friction and wear mechanisms. 58,59 This soft thermo-degraded layer can be removed quickly by abrasion due to sharp asperities or can prevent the rubber surface from further abrasion on less abrasive part of the surface (blunt asperities). Moreover, since these results were obtained from outdoor experiments, the effect of uncontrollable conditions such as some variations in ambient and asphalt temperature is unavoidable.…”
Section: Discussionmentioning
confidence: 99%